HRM practices and intention to stay: the moderating roles of organisational justice and generational diversity / Shariff Harun - Harun, Shariff (2019)
Previous studies suggested that there are many contributing factors influencing workers’ turnover intention in an organisation. However, what influences their decision to remain in an organisation has always been a complex and inconclusive research topic. Grounded by Herzberg’s Two Factor Theory, the Met Expectations Model, the Price and Muller’s Model of Turnover, and the Job Embeddedness Theory, combined with the Expectancy Theory Model, the Organisational Justice Theory and the Generational Theory, this study proposed a framework linking Human Resources Management (HRM) practices, organisational justice, generational diversity, and intention to stay. The need to analyse the factors affecting employees’ intention to stay, especially of the non-academic staff in Malaysian Private Higher Learning Institutions (PHLIs) is pertinent because the findings would be able to assist the universities to have better insights on what they should do to retain their competent workforce. In general, this study aims to examine the relationship between HRM practices and the intention to stay of non-academic staff within the context of Malaysian PHLIs. The effect of organisational justice was also studied to understand how the elements of fairness and justice influences the intention to stay of the non-academic staff. Subsequently, due to the diversity of the workforce that comes from different generational cohorts, this study also studied the effect of generational diversity in influencing the intention to stay of the non-academic staff. Data for this study were gathered through survey questionnaires and this study specifically examines the perceptions of the non-academic staff from the professional and management group of four selected Government Linked Universities (GLUs). The study found that Training and Performance Appraisal are two HRM practices most influential in determining the intention to stay of the non-academic staff. The results also suggested that two organisational justice dimensions, namely Justice – Management Practice, and Distributive Justice - Reward are important moderators, which have significant influences on the intention to stay of non-academic staff. In contrast, generational diversity was found to have no specific effect in influencing the non-academic staff intention to stay. This study hopes that the findings will be able to assist the management in PHLIs to manage their diverse workforce towards achieving the aspirations of Malaysia’s National Transformation 2050 (TN50). Finally, this research initiative can also help support one of the 12 National Key Economic Areas (NKEAs) initiatives, which is, transforming education as the engine of growth.